Molybdenum-induced effects on leaf ultra-structure and rhizosphere phosphorus transformation in Triticum aestivum L - Rana, Muhammad Shoaib (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.